An Analysis of Quartz Occurrence Patterns in Airborne Coal Mine Dusts - S. Padmanabhan; J. M. Mutmansky (The National Institute for Occupational Safety and Health (NIOSH), 1989)
"The subject of quartz occurrences in respirable coal mine dusts has been of increasing concern in recent years. The primary impetus for this concern has been provided by better measurement technology that has detected an increased number of mines with high quartz content in their respirable dusts. This paper presents the results of statistical analyses of quartz levels in multi-stage impactor samples from eighteen different coal mining sections located in Pennsylvania, West Virginia, Ohio, Illinois, Kentucky, Colorado and Ucah. The quartz and kaolinite determinations were then determined by combining impactor stage loadings to provide larger dust masses and applying the infrared spectrometry procedure outlined in Bureau of Mines/MSHA Method P7.The results will be presented using two categories of data collected during two separate phases of the research:(l) quartz concentration data from mines where quartz was known to be present in relatively high concentrations, and(2) quartz concentration data from mines chosen at random.The aspects of the occurrence of quartz in coal mine airborne dusts that will be reported include the size dependence of the quartz content, quartz variations with location in the mining section, and variations due to mining region. The results of the study show a strong pattern of size dependence of the quartz content in mines for which high quartz concentrations exist. A similar, though less pronounced, pattern exists in mines chosen at random. Quartz levels appear to have a varying relationship to section location and strong geographical patterns do not appear to exist in the data collected. Kaolinite content was found to be similar to that of quartz with patterns that are somewhat more consistent."